2016
DOI: 10.1177/1359105315586213
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in patients with advanced illness: The role of symptom control, resilience and social network

Abstract: In this study, we analyzed the relationships among clinical, emotional, social, and spiritual dimensions of patients with advanced illness. It was a cross-sectional study, with a sample of 108 patients in an advanced illness situation attended by palliative care teams. Statistically significant correlations were found between some dimensions of spirituality and poor symptomatic control, resiliency, and social support. In the structural model, three variables predicted spirituality: having physical symptoms as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
30
0
4
Order By: Relevance
“…Transcendent emotions from religion have been found to promote life satisfaction in middle-aged adults (Van Cappellen et al, 2016), but spiritual transcendence may be associated with distress in university students (Burris, Brechting, Salsman, & Carlson, 2009). Other research has found the size of one's social support network to correlate positively with interpersonal, negatively with transpersonal, and not at all with intrapersonal spirituality (Fombuena et al, 2016). Further research is needed to determine the role that spirituality may play and how each dimension functions in emerging adulthood.…”
Section: Spiritualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Transcendent emotions from religion have been found to promote life satisfaction in middle-aged adults (Van Cappellen et al, 2016), but spiritual transcendence may be associated with distress in university students (Burris, Brechting, Salsman, & Carlson, 2009). Other research has found the size of one's social support network to correlate positively with interpersonal, negatively with transpersonal, and not at all with intrapersonal spirituality (Fombuena et al, 2016). Further research is needed to determine the role that spirituality may play and how each dimension functions in emerging adulthood.…”
Section: Spiritualitymentioning
confidence: 99%
“…Many studies have demonstrated the important positive roles that spirituality can play for psychological well-being (Anum & Dasti, 2016;Foskett, Marriott, & Wilson, 2004;Porter, Brennan-Ing, Burr, Dugan, & Karpiak, 2017), life satisfaction (Koenig, 2007), and resilience (Fombuena et al, 2016;Smith & Carlson, 1997). Spirituality or religion may benefit the individual through many mechanisms (Oman & Thoresen, 2005).…”
Section: Spiritualitymentioning
confidence: 99%
See 3 more Smart Citations